Seismic Design and Testing of Post-tensioned Timber Buildings With Dissipative Bracing Systems - Ponzo, Felice Carlo; Di Cesare, Antonio; Lamarucciola, Nicla; Nigro, Domenico (Frontiers in Built Environment, 2019)
This paper describes a seismic design procedure for low-damage buildings composed by post-tensioned timber framed structures coupled with hysteretic dissipative bracing systems. The main goal of the design procedure is preventing or limiting earthquake induced damage to the structural and no-structural elements. For this aim, a target design displacement is defined according to the desired performance level. Then, the corresponding design force, strength and stiffness of the post-tensioning and of the dissipative braces are evaluated in order to size post-tensioned connections and dissipating devices. The results of shaking table testing performed at the University of Basilicata are also reported. A prototype model, 2/3 scaled, 3-dimensional, 3-storey with post-tensioned timber structure without and with V-inverted braces and U-shaped flexural steel dampers has been extensively tested. During testing, the specimen was subjected to a set of seven earthquakes at different intensity levels of the peak ground acceleration. The effectiveness of the bracing system and the reliability of the proposed procedure are experimentally demonstrated. Nonlinear dynamic analyses have been performed in order to simulate the experimental seismic response. The numerical model is based on lumped plasticity approach, which combines the use of elastic elements with linear and rotational springs representing energy dissipating devices and plastic rotations of the connections. The numerical results accurately predict the nonlinear behavior of the prototype model, obtaining a satisfactory matching with the target drift considered for design.